2017
DOI: 10.1016/j.bandl.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure integrity in relation to reading proficiency☆

Abstract: Components of reading proficiency such as accuracy, fluency, and comprehension require the successful coordination of numerous, yet distinct, cortical regions. Underlying white matter tracts allow for communication among these regions. This study utilized unique residualized tract – based spatial statistics methodology to identify the relations of white matter microstructure integrity to three components of reading proficiency in 49 school - aged children with typically developing phonological decoding skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 50 publications
5
35
1
Order By: Relevance
“…Consistent with our hypothesis, the association between mean fractional anisotropy of the UF‐R and core language scores was moderated by birth group. The exact function of the uncinate fasciculus is debated; however, the present findings are consistent with prior studies that have found associations between properties of the uncinate fasciculus and language and reading abilities . The uncinate fasciculus connects with anterior projections of the inferior fronto‐occipital fasciculus, a tract considered in cognitive models of language and reading to be part of the ventral stream, and to be relevant for mapping sound to meaning.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our hypothesis, the association between mean fractional anisotropy of the UF‐R and core language scores was moderated by birth group. The exact function of the uncinate fasciculus is debated; however, the present findings are consistent with prior studies that have found associations between properties of the uncinate fasciculus and language and reading abilities . The uncinate fasciculus connects with anterior projections of the inferior fronto‐occipital fasciculus, a tract considered in cognitive models of language and reading to be part of the ventral stream, and to be relevant for mapping sound to meaning.…”
Section: Discussionsupporting
confidence: 90%
“…The exact function of the uncinate fasciculus is debated; however, the present findings are consistent with prior studies that have found associations between properties of the uncinate fasciculus and language and reading abilities. 20,39 The uncinate fasciculus connects with anterior projections of the inferior fronto-occipital fasciculus, a tract considered in cognitive models of language and reading to be part of the ventral stream, 34 and to be relevant for mapping sound to meaning. A previous study demonstrated altered white matter properties in the uncinate fasciculus in adolescents born preterm compared with peers born at term, and found associations between fractional anisotropy of the UF-R and scores on a semantic language task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, inter-individual variations in the microstructural properties of both the left and right ILFs in people with normal intelligence are correlated with word reading fluency and reading comprehension ( Horowitz-Kraus et al, 2014 ). This agrees with the fact that difficulties in reading comprehension were found to be associated with abnormalities of the right ILF in adolescents born preterm ( Feldman et al, 2012 ) and abnormalities of the left ILF in poor decoders ( Arrington et al, 2017 ). Lastly, these findings are consistent with the observation that the rate of maturation of the ILF covaries with children’s reading abilities ( Yeatman et al, 2012 ).…”
Section: Functions Mediated By the Ilfsupporting
confidence: 89%